Synergistic Co-pyrolysis of Lignin and Cellulose for Fabricating Porous Carbon Applied in Supercapacitors - Barton, Anders; Tuyan, Sunil; Resin, Laurent (Journal of Green Energy and Environmental Engineering, 2023)
Using enzymatic hydrolysis lignin and cellulose-containing waste textiles as co-precursors, with lignin and cellulose serving as composite carbon sources, porous carbon (TLPC) with a high specific surface area for supercapacitor applications was successfully prepared via a one-step carbonization-activation method. The microporous structure and electrochemical performance of the TLPC samples were systematically investigated. The results showed that at a carbonization temperature of 800 °C, the prepared TLPC-800 exhibited a high specific capacitance of 275 F/g at a current density of 0.5 A/g. When assembled into a symmetrical supercapacitor, the device delivered an energy density of 13.54 Wh/kg at a power density of 325 W/kg. After 10,000 charge-discharge cycles, the capacitance retention rate reached nearly 99.6% with a coulombic efficiency of approximately 100%, indicating excellent cycling stability. Furthermore, the assembled large-volume flexible solid-state supercapacitor also demonstrated favorable electrochemical performance.